Chairing the internal medicine department- analysis of current state and future trends in Israel - Dana Zelnik Yovel; Orna Tal; Dror Dicker; Avishay Elis; Micha Rapoport (BMC, 2018)
Abstract Background Professional skills and academic records of the highest degree are essential requirements for the chairmanship of internal medicine departments. Whether the new generation and future successors of Israeli chairmen is endowed with these attributes is not known. Purpose To determine whether there is a lack of future suitable successors for the current heads of internal medicine departments in Israel and to compare the demographic, academic and professional characteristics of the older and newer generations of department heads. Methods An online anonymous questionnaire was nationally distributed during 2016 to all active heads of internal medicine departments in Israel (n = 101). First round was followed by two runs of personal phone calls to promote participation. Results Sixty-seven (67%) of chairmen responded. The vast majority of current chairs of internal medicine departments are males (N = 59, 88%) over 50 years of age (N = 58, 86%) with established academic background with lecturer degree or higher (N = 57, 85%). Only 19 (28%) of current heads assigned a future successor. Comparison of chairmen who did and did not assigned successors demonstrated that assignment of successors was associated with higher academic status (P < 0.02) and longer chairmanship (p < 0.01) but not with mean age of current chairmen (p < 0.08). Nevertheless, most assignments (55%) were done by chairmen in the 61 to 67 years age group. As compared to current chairmen, the designated successors have lesser academic status (p < 0.01) and are characterized by a higher female prevalence (P < 0.03). Conclusions Significant demographic, professional and academic differences exist between the current chairs of internal medicine departments in Israeli hospitals and their future successors. This underscores the need for reassessment of the availability and requirements of this crucial position.